The importance of aeration mode and flowrate in the determination of the biological activity and stability of organic wastes by respiration indices. (November 2015) - Almeira, Natividad; Komilis, Dimitrios; Barrena, Raquel; Gea, Teresa; Sánchez, Antoni
Highlights: The importance of aeration on compost activity and stability was assessed. Airflow rates were studied using constant and adjustable modes. The 'controlled respiration' mode resulted in the highest respiration activity. Respiration activity was limited at constant flows below 20 L kg −1 DM h −1 . Above an aeration volume of 3000 L kg −1 DM, respiration activity was constant. Abstract: The aim of this study was to assess the effect of different air flowrates and different aeration modes on the respiration activity of three organic substrates of different stability degree: (i) a constant flowrate and (ii) a continuously adjusted air flowrate that optimized the oxygen uptake rate (OUR). Above 20 L air kg −1 DM h −1, at the constant flow regime, the resulting dynamic respiration index at 24 h (DRI24 ) and the cumulative respiration at four days (AT4 ) were statistically similar. At the OUR based aeration regime, the DRI24 and AT4 were statistically similar at all initial flowrates tested. Above a minimum threshold, cumulative air flow of around 3000 L air kg −1 DM during a 5 day period, the respiration activity was similar, particularly for the two less active substrates. This study highlights the importance of selecting the aeration to obtain reliable measures of biological activity and stability in organic wastes.